2003
DOI: 10.1007/s11926-003-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic cardiovascular disease in rheumatoid arthritis

Abstract: The past 3 years have seen a remarkable growth in the interest of cardiovascular disease in rheumatoid arthritis. There have been studies published documenting an increased incidence and prevalence of cardiovascular conditions in patients with rheumatoid arthritis compared with individuals without rheumatoid arthritis. There has also been interest in the occurrence of cardiovascular risk factors in rheumatoid arthritis and in the role of antirheumatic therapy, including cyclooxygenase-2 selective nonsteroidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 66 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…RA patients tend to have an increased risk of developing atherosclerosis due to the disease itself and the long-standing immunosuppressive therapy with corticosteroids leading to increased morbidity by coronary, cerebral and PAD [25,26]. Relevant PAD is considered in patients with an ankle-brachial index <0.9 [27].…”
Section: Discussionmentioning
confidence: 99%
“…RA patients tend to have an increased risk of developing atherosclerosis due to the disease itself and the long-standing immunosuppressive therapy with corticosteroids leading to increased morbidity by coronary, cerebral and PAD [25,26]. Relevant PAD is considered in patients with an ankle-brachial index <0.9 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease associated with an accelerated atherosclerosis (24, 25), which is responsible for an increased cardiovascular (CV) morbidity and mortality (26). The chronic systemic inflammatory status, independent of the traditional CV risk factors, plays a pivotal role in the development of the accelerated atherogenesis observed in the patients with RA (24, 27–30). Interestingly, elevated levels of VEGF have been observed in the serum of patients with RA (31) and these levels seem to be correlated with the severity of the disease (32).…”
Section: Introductionmentioning
confidence: 99%
“…9,26 Also, it has been reported that patients with RA have mortality rates higher than those of the general population, with most deaths due to complications of arteriosclerosis. 10,29,30 Patients with RA were also found to have increased intima-media thicknesses, a factor strongly associated with adverse cardiovascular events. 29 A meta-analysis by Tyrrell et al 7 showed that patients with rheumatic disease have a higher occurrence of atherosclerosis as determined by ultrasonographically measured intima-media thickness.…”
Section: Discussionmentioning
confidence: 99%
“…10,29,30 Patients with RA were also found to have increased intima-media thicknesses, a factor strongly associated with adverse cardiovascular events. 29 A meta-analysis by Tyrrell et al 7 showed that patients with rheumatic disease have a higher occurrence of atherosclerosis as determined by ultrasonographically measured intima-media thickness. Therefore, when treating such patients, clinicians should address their increased risk of atherosclerosis and cardiovascular disease by making efforts to mitigate cardiovascular risk factors and control disease symptoms, including inflammation.…”
Section: Discussionmentioning
confidence: 99%